Проблема развития лингво-культурологических компетенций на уроках русского языка в 5-6 классах - Мисяченко, С.В. (My University, 2016)
The article presents the development of linguoculturological competencies at the lessons of the Russian language in 5-6 forms. It analyses the examples which represent the cultural values and review the national culture.
Keywords: the Russian language; the lesson; linguoculturological; the competency; the culture